SELECTING SUITABLE ANTI-BROWNING AGENTS FOR MINIMALLY PROCESSED POTATO TECHNOLOGICAL PROCESSES - Le Thi My Chau*, Pham Dinh Nhat Trung, Vo Thi My Tam; Dang Thi Anh Tuyet (Tạp chí Khoa học)
Minimal processing is a trend in modern processing technology that meets the evolving needs of society. The study determined the physicochemical properties of the potato raw materials used. Develop a suitable minimum processing for potatoes used in research: Soaking in 0.05% NaHSO3 solution at 15 ÷ 30˚C for 15 minutes for shaping into bars and slides, 20 minutes for cubes; Packing in plastic; after storage at cold temperature. The minimum shelf-life of processed potatoes when processed and stored under selected conditions is 6 ÷ 8 days, compared to 1 ÷ 2 days when cut potatoes are washed with clean water and stored at the same temperature.